Effect of oxygen and hydrogen plasma treatment on the room temperature sensitivity of SnO2 gas sensors - Srivastava R.; Dwivedi R.; Srivastava S.K. (My University, 2025)
The influence of oxygen plasma as well as hydrogen plasma on the gas sensing properties of palladium doped SnO2 has been studied. It is found that the sensors treated in gaseous plasma become sensitive at room temperature and the sensitivity increases with the duration of exposure in gaseous plasma. The sensitivity of sensors treated in oxygen plasma is found to be about 10 times more than that of untreated sensor, while in the case of hydrogen plasma it is about seven times when treated for 15 min. The response and recovery time has also been studied. It is found that both the response time and recovery time decrease with the increase in the duration of exposure time. The barrier height and effective barrier characteristics have also been evaluated through the low temperature and impedance spectroscopic measurements. © 1998 Elsevier Science Ltd. All rights reserved.